2017
DOI: 10.1073/pnas.1620954114
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S is the major activator of the psoriasis-associated proinflammatory cytokine IL-36γ

Abstract: The proinflammatory cytokine IL-36γ is highly expressed in epithelial cells and is a pivotal mediator of epithelial inflammation. In particular, IL-36γ is strongly associated with the inflammatory skin disease psoriasis. As with other IL-1 cytokines, IL-36γ is expressed as an inactive precursor and must be processed by specific proteases to become bioactive. Our aim therefore was to identify protease/s capable of IL-36γ activation and explore the importance of this activation in psoriasis. Using a keratinocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
124
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 48 publications
(61 reference statements)
9
124
2
Order By: Relevance
“…3B) do not resemble caspase-1 sites (73,74). In vitro, neutrophil-derived cathepsin G, elastase, and proteinase-3 can truncate full-length recombinant IL-36 and IL-36Ra proteins (74)(75)(76); however, whether this processing is activating or inactivating is currently controversial (74)(75)(76). Note that several of these proteases have been reported to also cleave IL-1b (Fig.…”
Section: Cytokine Activation Mechanismsmentioning
confidence: 98%
“…3B) do not resemble caspase-1 sites (73,74). In vitro, neutrophil-derived cathepsin G, elastase, and proteinase-3 can truncate full-length recombinant IL-36 and IL-36Ra proteins (74)(75)(76); however, whether this processing is activating or inactivating is currently controversial (74)(75)(76). Note that several of these proteases have been reported to also cleave IL-1b (Fig.…”
Section: Cytokine Activation Mechanismsmentioning
confidence: 98%
“…This indicated that sufficient IL-17A was still present in these supernatants that stimulated gene expression. As mentioned above, IL-36 cytokines require processing to gain biological activity [34][35][36] . IL-36 can be processed and activated by proteases derived from neutrophils 25,36 .…”
Section: Resultsmentioning
confidence: 99%
“…3e and Supplementary Fig. S3a) 25,[34][35][36]53 . Together, these observations suggest that IL-36 and its processing factors are likely to be important in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations